Chemically stable multilayered covalent organic nanosheets from covalent organic frameworks via mechanical delamination - Chandra, Suman; Kandambeth, Sharath; Biswal, Bishnu P.; Lukose, Binit; Kunjir, Shrikant M.; Chaudhary, Minakshi V.; BabaRao, Ravichandar; Heine, Thomas; Banerjee, Rahul (Journal of the American Chemical Society, 2013)
A series of five thermally and chemically stable functionalized covalent organic frameworks (COFs), namely, TpPa-NO2, TpPa-F-4, TpBD-(NO2)(2), TpBD-Me-2, and TpBD-(OMe)(2) were synthesized by employing the solvothermal aldehyde-amine Schiff base condensation reaction. In order to complete the series, previously reported TpPa-1, TpPa-2, and TpBD have also been synthesized, and altogether, eight COFs were fully characterized through powder X-ray diffraction (PXRD), Fourier transform IR (FT-IR) spectroscopy, C-13 solid-state NMR spectroscopy, and thermogravimetric analysis. These COFs are crystalline, permanently porous, and stable in boiling water, acid (9 N HCl), and base (3 N NaOH). The. synthesized COFs (all eight) were successfully delaminated using a simple, safe, and environmentally friendly mechanical grinding route to transform into covalent organic nanosheets (CONs) and were well characterized via transmission electron microscopy and atomic force microscopy. Further PXRD and FT-IR analyses confirm that these CONs retain their structural integrity throughout the delamination process and also remain stable in aqueous, acidic, and basic media like the parent COFs. These exfoliated CONs have graphene-like layered morphology (delaminated layers), unlike the COFs from which they were synthesized.

Chemical sensing in two dimensional porous covalent organic nanosheets - Das, Gobinda; Biswal, Bishnu P.; Kandambeth, Sharath; Venkatesh, V.; Kaur, Gagandeep; Addicoat, Matthew A.; Heine, Thomas; Verma, Sandeep; Banerjee, Rahul (Chemical Science, 2015)
Two new imide-based crystalline, porous, and chemically stable covalent organic frameworks (COFs) (TpBDH and TfpBDH) have been successfully synthesized employing solvothermal crystallization route. Furthermore, thin layered covalent organic nanosheets (CONs) were derived from these bulk COFs by the simple liquid phase exfoliation method. These 2D CONs showcase increased luminescence intensity compared to their bulk counterparts (COFs). Notably, TfpBDH-CONs showcase good selectivity and prominent, direct visual detection towards different nitroaromatic analytes over TpBDH-CONs. Quite interestingly, TfpBDH-CONs exhibit a superior ``turn-on'' detection capability for 2,4,6-trinitrophenol (TNP) in the solid state, but conversely, they also show a ``turn-off'' detection in the dispersion state. These findings describe a new approach towards developing an efficient, promising fluorescence chemosensor material for both visual and spectroscopic detection of nitroaromatic compounds with very low [10(-5) (M)] analyte concentrations.

Chemically delaminated free-standing ultrathin covalent organic nanosheets - Khayum, M. Abdul; Kandambeth, Sharath; Mitra, Shouvik; Nair, Sanoop B.; Das, Anuja; Nagane, Samadhan S.; Mukherjee, Rabibrata; Banerjee, Rahul (Angewandte Chemie-International Edition, 2016)
Covalent organic nanosheets (CONs) are a new class of porous thin two-dimensional (2D) nanostructures that can be easily designed and functionalized and could be useful for separation applications. Poor dispersion, layer restacking, and difficult postsynthetic modifications are the major hurdles that need to be overcome to fabricate scalable CON thin films. Herein, we present a unique approach for the chemical exfoliation of an anthracene-based covalent organic framework (COF) to N-hexylmaleimide-functionalized CONs, to yield centimeter-sized free-standing thin films through layer-by-layer CON assembly at the air-water interface. The thinlayer fabrication technique presented here is simple, scalable, and does not require any surfactants or stabilizing agents.

Constructing covalent organic frameworks in water via dynamic covalent bonding - Thote, Jayshri; Aiyappa, Harshitha Barike; Kumar, Raya Rahul; Kandambeth, Sharath; Biswal, Bishnu P.; Shinde, Digambar Balaji; Roy, Neha Chaki; Banerjee, Rahul (Iucrj, 2016)
The formation of keto-enamine based crystalline, porous polymers in water is investigated for the first time. Facile access to the Schiff base reaction in water has been exploited to synthesize stable porous structures using the principles of Dynamic Covalent Chemistry (DCC). Most credibly, the water-based Covalent Organic Frameworks (COFs) possess chemical as well as physical properties such as crystallinity, surface area and porosity, which is comparable to their solvothermal counterparts. The formation of COFs in water is further investigated by understanding the nature of the monomers formed using hydroxy and non-hydroxy analogues of the aldehyde. This synthetic route paves a new way to synthesize COFs using a viable, greener route by utilization of the DCC principles in conjunction with the keto-enol tautomerism to synthesize useful, stable and porous COFs in water.

Convergent covalent organic framework thin sheets as flexible supercapacitor electrodes - Khayum, Abdul M.; Vijayakumar, Vidyanand; Karak, Suvendu; Kandambeth, Sharath; Bhadra, Mohitosh; Suresh, Karthika; Acharambath, Nikhil; Kurungot, Sreekumar; Banerjee, Rahul (ACS Applied Material & Interfaces, 2018)
Flexible supercapacitors in modern electronic equipment require light-weight electrodes, which have a high surface area, precisely integrated redox moieties, and mechanically strong flexible free-standing nature. However, the incorporation of the aforementioned properties into a single electrode remains a great task. Herein, we could overcome these challenges by a facile and scalable synthesis of the convergent covalent organic framework (COF) free-standing flexible thin sheets through solid-state molecular baking strategy. Here, redox-active anthraquinone (Dq) and pi-electron-rich anthracene (Da) are judiciously selected as two different linkers in a beta-ketoenamine-linked two-dimensional (2D) COF. As a result of precisely integrated anthraquinone moieties, COF thin sheet exhibits redox activity. Meanwhile, pi-electron-rich anthracene linker assists to improve the mechanical property of the free-standing thin sheet through the enhancement of noncovalent interaction between crystallites. This binder-free strategy offers the togetherness of crystallinity and flexibility in 2D COF thin sheets. Also, the synthesized porous crystalline convergent COF thin sheets are benefited with crack-free uniform surface and light-weight nature. Further, to demonstrate the practical utility of the material as an electrode in energy-storage systems, we fabricated a solid-state symmetrical flexible COF supercapacitor device using a GRAFOIL peeled carbon tape as the current collector.

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, Sharath; Dey, Kaushik; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.